2023
DOI: 10.1021/acs.energyfuels.3c01006
|View full text |Cite
|
Sign up to set email alerts
|

Cu–Ni Alloy Nanoparticles Anchored on Nitrogen-Doped Carbon Nanotubes for Efficient CO2 Electroreduction to CO

Abstract: Efficient conversion of CO2 to value-added fuels or chemicals using electricity from renewable sources is an appealing approach to realize carbon neutrality. Under this background, it is crucial to design efficient and low-cost catalysts for CO2 electroreduction. Herein, we fabricated an electrocatalyst with the structure of Cu–Ni alloy nanoparticles grown on nitrogen-doped carbon nanotubes (Cu x Ni/NCNT, x = 2.4, 1, and 0.36) for electrochemical CO2 reduction reaction (CO2RR) via a hydrothermal method followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…32,33 The production of CO involved Cu−Ni alloy nanoparticles. 34 In the case of Cu 1−x Ni x , an increase in Ni content shifted the major products from C 2 compounds (C 2 H 4 and C 2 H 5 OH) to C 1 products (CH 4 and HCOO − ). 35 The support effect played a crucial role in the C 2 H 5 OH production of NiCu alloy on carbon nanofibers, involving the dimerization of CO. 36 For CuNiZn alloy, 40,41 Park et al demonstrated formate as the dominant product in a 0.1 M KHCO 3 electrolyte, with the additional meaningful production of long-chain C 2−7 hydrocarbons (C n H 2n+2 and C n H 2n ), explained by FT synthesis.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…32,33 The production of CO involved Cu−Ni alloy nanoparticles. 34 In the case of Cu 1−x Ni x , an increase in Ni content shifted the major products from C 2 compounds (C 2 H 4 and C 2 H 5 OH) to C 1 products (CH 4 and HCOO − ). 35 The support effect played a crucial role in the C 2 H 5 OH production of NiCu alloy on carbon nanofibers, involving the dimerization of CO. 36 For CuNiZn alloy, 40,41 Park et al demonstrated formate as the dominant product in a 0.1 M KHCO 3 electrolyte, with the additional meaningful production of long-chain C 2−7 hydrocarbons (C n H 2n+2 and C n H 2n ), explained by FT synthesis.…”
Section: Introductionmentioning
confidence: 93%
“…In the Cu 2p XPS profiles (Figure 9a), Cu 2p 3/2 and Cu 2p 1/2 peaks at 932.2 and 952.1 eV, respectively, were assigned to Cu/ Cu 2 O. 15,34,35,40 The Cu 2p 3/2 peak at 934.4 eV, attributed to CuO, 15,34,35,40 was distinctly observed and removed after sputtering. The CuO peak became much weaker after the EC test at −2.0 V (Figure 9b).…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
See 3 more Smart Citations